Representing others in a public good game - Karen Evelyn Hauge; Ole Rogeberg (Games, 2015)
In many important public good situations the decision-making power and authority is delegated to representatives who make binding decisions on behalf of a larger group. The purpose of this study is to compare contribution decisions made by individuals with contribution decisions made by group representatives. We present the results from a laboratory experiment that compares decisions made by individuals in inter-individual public good games with decisions made by representatives on behalf of their group in inter-group public good games. Our main finding is that contribution behavior differs between individuals and group representatives, but only for women. While men's choices are equally self-interested as individuals and group representatives, women make less self-interested choices as group representatives.
Keywords: 330; public good game; lab experiment; group representative; gender